Activation of the Fibrinolytic System in Patients with Coronary Artery Disease and Hyperfibrinogenemia - Stein, D; Heins, M; Schoebel, F C; Pels, K; Jax, T W; Stiegler, H; Reinauer, H; Strauer, B E; Leschke, M (Thrombosis and Haemostasis, 1997)
Elevated fibrinogen levels as well as an impaired activity of the fibrinolytic system are regarded as important cardiovascular risk factors. To elucidate a potential interrelation between fibrinogen as an indicator of a hypercoagulable state and the endogenous fibrinolytic function hemostatic and rheological as well as lipid parameters were determined in 224 consecutive patients, who underwent elective coronary angiography. In the selected study population of 81 men and 19 women with fibrinogen concentrations either ≥3.5 g/1 (n = 70) or ≤2.5 g/1 (n = 30) hyperfibrinogenemia was found to be significantly associated with increased concentrations of plasmin-α2-antiplasmin complex [PAP [median (25.-75. percentile)], 534 (361-680) μg/l vs. 289 (243-440) μg/1; p <0.001] and tissue plasminogen activator (t-PA) antigen [9 (6-11) μg/1 vs. 8 (5-9) |xg/l; p <0.05] while this association was lost in the subgroup of patients with angiographically normal coronary arteries (n = 26). In addition to these findings fibrinogen was significantly correlated with PAP (r = 0.40, p <0.001; n = 224) and t-PA antigen (r = 0.2, p <0.01; n = 224) after adjustment for age, diabetes mellitus, lipid parameters and leucocyte counts. It can be argued that elevated fibrinogen levels in patients with coronary artery disease are concomitant with an activation of the fibrinolytic system.